2019
DOI: 10.1093/tas/txz042
|View full text |Cite
|
Sign up to set email alerts
|

Cattle stratified on genetic merit segregate on carcass characteristics, but there is scope for improvement1

Abstract: Abstract The study objective was to quantify the ability of genetic merit for a generated carcass index to differentiate animals on primal carcass cut weights using data from 1,446 herds on 9,414 heifers and 22,413 steers with weights for 14 different primal carcass cuts (plus 3 generated groups of cuts). The carcass genetic merit index was compromised of carcass weight (positive weight), conformation (positive weight), and fat score (negative weight), each equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In fact, Connolly et al (2019) reported that animals in the top 25% for a terminal index had a greater predicted yield of higher value carcass cuts as well as more total meat yield, relative to animals in the bottom 25%; cut yields were predicted from video image analysis ( Pabiou et al, 2011 ). Similarly, Berry et al (2019b) , using actual primal-cut weight data, reported that the weight of primal cuts increased almost linearly with increasing genetic merit for a total merit terminal index. Thus, beef cattle of high total genetic merit for a terminal index are expected to yield carcasses of superior quality and value, in comparison to their low total genetic merit counterparts, which helps ensure economic sustainability for both the primary producer and the abattoir.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In fact, Connolly et al (2019) reported that animals in the top 25% for a terminal index had a greater predicted yield of higher value carcass cuts as well as more total meat yield, relative to animals in the bottom 25%; cut yields were predicted from video image analysis ( Pabiou et al, 2011 ). Similarly, Berry et al (2019b) , using actual primal-cut weight data, reported that the weight of primal cuts increased almost linearly with increasing genetic merit for a total merit terminal index. Thus, beef cattle of high total genetic merit for a terminal index are expected to yield carcasses of superior quality and value, in comparison to their low total genetic merit counterparts, which helps ensure economic sustainability for both the primary producer and the abattoir.…”
Section: Discussionmentioning
confidence: 92%
“… Connolly et al (2016) for example, using a national database, illustrated that genetically elite cattle (i.e., top 25% for a terminal index) had, on average, heavier and better conformed carcasses, with less fat cover, relative to animals of low genetic merit (i.e., bottom 25% for a terminal index). Berry et al (2019b) extended this, documenting heavier yields of higher value primal carcass cuts in cattle excelling on the Irish terminal index. Nevertheless, apart from experimental studies with a relatively small number of animals ( Clarke et al, 2009 ), few have attempted to quantify the association between animal total merit index, feed intake, and efficiency in beef cattle.…”
Section: Introductionmentioning
confidence: 83%
“…Proper and transparent validation of any new tool is crucial to its acceptance by industry. Breeding goals can be validated using a controlled experimental study (Clarke et al, 2009a;Coleman et al, 2009) or a crosssectional analysis of a large data set; the latter can be undertaken at the level of the animal (Connolly et al, 2016;Berry et al, 2019c;Twomey et al, 2020) or the herd (Ramsbottom et al, 2012). Berry and Ring (2020a) used a data set of 123,785 calving records and carcass information from 48,875 animals to validate the dairy-beef index proposed by Berry et al (2019a); of particular interest in their validation study was a comparison with the status quo of selecting beef bulls for use on Irish dairy females based on a combination of genetic merit for easy calving and short gestation.…”
Section: Beef-on-dairy Breeding Goalsmentioning
confidence: 99%